2021
DOI: 10.15557/jou.2021.0006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of parenchymal vascularity of the thyroid gland with vascularization index by color superb microvascular imaging in patients with Graves’ disease

Abstract: Aim of the study: To determine the parenchymal vascularity of the thyroid gland with color superb microvascular imaging in patients with Graves’ disease, and compare the vascularization index values with healthy subjects. Materials and methods: The thyroid glands of 37 patients whose laboratory and clinical findings were consistent with Graves’ disease, and 40 asymptomatic subjects with normal laboratory values, were examined using color superb microvascular imaging. Measurements of the vascularization index w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In addition to showing subtle flow signals in thyroid nodules, SMI also plays an important role in the diagnosis and differential diagnosis of diffuse thyroid disease. Kilincer et al 50 found in patients with goiter, the distribution of blood vessels changes with the different stages of thyroid function, the vessel density in patients with toxic goiter is significantly higher than those with non‐toxic goiter. Joonghyun Yoo found SMI was more sensitive to detect changes in the number and distribution of vessels in patients with thyroiditis and hyperthyroidism than CDFI.…”
Section: Application Of Smi In Thyroidmentioning
confidence: 98%
“…In addition to showing subtle flow signals in thyroid nodules, SMI also plays an important role in the diagnosis and differential diagnosis of diffuse thyroid disease. Kilincer et al 50 found in patients with goiter, the distribution of blood vessels changes with the different stages of thyroid function, the vessel density in patients with toxic goiter is significantly higher than those with non‐toxic goiter. Joonghyun Yoo found SMI was more sensitive to detect changes in the number and distribution of vessels in patients with thyroiditis and hyperthyroidism than CDFI.…”
Section: Application Of Smi In Thyroidmentioning
confidence: 98%
“…studies. In only a few of these studies, the new version of VI, which gives us a quantitative value, was used (19,20,21). In our study, the new version of VI, which gives numeric values, was used.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%